Efficient anomalous valley Hall effect switching in antiferrovalley MnSe driven by magnetoelectric coupling - Yaping Wang; Xinguang Xu; Weixiao Ji; Wei Sun; Shengshi Li; Yanlu Li; Xian Zhao (Journal of Materiomics)
The exploration of two-dimensional antiferrovalley materials as potential candidates for valleytronics offers intriguing prospects to investigate exotic valley physics and develop next-generation nano-electronic devices. Achieving efficient anomalous valley Hall effect (AVHE) switching in antiferrovalley materials constitutes an important step towards their application, yet such advancement has been scarcely reported so far. In this study, we demonstrate, through first-principles calculations and model analysis, that the experimentally synthesized MnSe monolayer is a hitherto unexplored but exceptional antiferrovalley material with spontaneous valley polarization. And more importantly, by constructing a multiferroic MnSe/In2Se3 heterostructure, the desired nonvolatile on/off switching of the AVHE can be successfully realized through polarization reversal. This unique phenomenon, characterized by the emergence/annihilation of fully spin-polarized valley polarization, arises from the combined effect of strong magnetoelectric coupling-induced changes in magnetic anisotropy and PT symmetry breaking. Our findings provide a novel approach for achieving nonvolatile control of the AVHE in antiferrovalley materials, opening up significant opportunities for valleytronic applications.